Does market orientation pay off without brand orientation? A study of small business entrepreneurs. Issue 7 (3rd May 2016) - Laukkanen, Tommi; Tuominen, Sasu; Reijonen, Helen; Hirvonen, Saku
ABSTRACT: Market orientation and brand orientation are usually modelled as distinct antecedents of business performance, and the simultaneous performance effects of these orientations are empirically under-explored. Moreover, studies of market orientation and branding tend to focus on large corporations and the views of managers rather than the views of small business entrepreneurs. Addressing these research gaps, the current study explores market orientation and brand orientation by empirically testing their simultaneous effects on the business performance of small firms. Using primary data from 328 effective responses gathered from small business entrepreneurs, the study finds that market orientation improves the financial performance of a small firm only if it is implemented through brand orientation and eventually translated into brand performance. The results further indicate that older firms benefit more than younger firms from investing in branding, while younger firms benefit from paying attention to the actions of their rivals.